(untitled) (Archive of Conferences, 2021)
The COVID-19 pandemic has led to the largest disruption to education systems in history, affecting nearly 1.6 billion students in more than 190 countries and all continents. At the same time, it should be noted that the crisis served as a stimulus for innovation in the field of education. Innovative approaches are being taken to ensure the continuity of education and training, from radio and television broadcasts to the provision of home study kits. Distance learning solutions have been developed as a result of the rapid response measures taken to ensure a seamless learning experience by governments and partners around the world. [2] The COVID-19 pandemic has become a major challenge for higher medical education, creating challenges, especially for teaching clinical subjects and clinical skills, as this process requires contact teaching of students.